Innovation in the time of SARS-CoV-2: A collaborative journey between NHS clinicians, engineers, academics and industry. Issue 5 (October 2021) - Din, Ahmed Riaz; Althoefer, Kaspar; Farkhatdinov, Ildar; Brown, Joshua; Morgan, Claire; Shahdad, Shakeel
Abstract: During the pandemic healthcare faced great pressure on the availability of protective equipment. This paper describes the entire novel innovative process of design optimisation, production and deployment of face-visors to NHS frontline workers during SARS-CoV-2 pandemic. The described innovative journey spans collaboration between clinicians and academic colleagues for design to the implementation with industry partners of a face-visor for use in a healthcare setting. It identifies the enablers and barriers to development along with the strategies employed to produce a certified reusable, adjustable, high volume and locally produced face-visor. The article also explores aspects of value, scalability, spread and sustainability all of which are essential features of innovation. Highlights: Innovation within dentistry and healthcare needs to be embraced. Collaboration with academic and industry partners results in successful outcomes. Academic syllabuses need new avenues of learning and collaboration.